Reflexões sobre a Psicologia como ciência a partir da fenomenologia de Martin Heidegger - Carminholi, Carla Caminata (2015)
This dissertation aims to discuss the metaphysical context upon which Psychology established itself as Science departing from the phenomenological method of Martin Heidegger such as laid down, mainly, in Being and Time. The dissertation also aims at presenting how this method suspends, from the human being, the definition of subject imposed onto it all along the History of Philosophy. Ever since Plato and Aristotle, Philosophy veils the question concerning the sense of being . Ever since, Philosophy and Metaphysics are mingled in the attempt to represent determinate regions of entities. Further on, French philosopher René Descartes, while attempting to set down safe paths for Science, drives even farther away the originary foundation later unfolded by Heidegger. In such a scientific context one attributes to the human being the determination of subject, as that which is capable of knowing, in opposition to the object, that is, to all the other entities which do not possess reason as a peculiar characteristic. Psychology raises itself as Science departing from such a presupposition, conceiving consciousness as its object of study. But when Heidegger describes the mode-of-being of the human being as Dasein, he allows that it no longer be defined as subject, but rather as an entity which exists and that arouses a large array of interests in the psychological field. This dissertation, therefore, is divided in three chapters: the first intends to show the metaphysical and scientific contexts upon which Psychology comes to be established; the second presents Heidegger s phenomenological method and his description of the mode-of-being of Dasein; the third, in conclusion, points out to possible contributions of Heidegger s thinking to the sphere of Psychology